The rise of unmanned gyms: innovation, spatiotemporal characteristics, and the future of urban fitness - Peng, Tianhang; Liang, Wanyuan; Zhang, Jiayi; Zhang, Zike (Frontiers in Sports and Active Living, 2025)
With the acceleration of urbanization and the growing awareness of health, traditional gyms face challenges related to space, time, and operational costs, particularly in meeting the fragmented fitness needs of urban residents. Unmanned gyms, integrating advanced technologies such as the Internet of Things (IoT) and Artificial Intelligence (AI), provide flexible, personalized fitness solutions available 24/7, addressing the increasing fitness demands of modern urban populations. Moreover, through innovative business models such as dynamic pricing, data monetization, and value-added services, unmanned gyms optimize their revenue structures and enhance user experiences. However, despite their significant growth potential, unmanned gyms still face challenges in terms of technology, ethics, and regulation. This paper reviews the current development of unmanned gyms, their spatiotemporal characteristics, and future trends. Future research should focus on the sustainability of technologies, user engagement, and the improvement of regulatory frameworks to foster the healthy growth of the unmanned gym industry.